The Effect of Adenosine Monophosphate, Arcaine and Anti-Inflammatory Agents on Thrombosis and Platelet Function in Rabbits - Peterson, Jane; Zucker, Marjorie B. (Thrombosis and Haemostasis, 1970)
Thrombi were produced by exposing femoral veins of rabbits to sodium morrhuate followed by partial ligation. The incidence of occlusive thrombosis in 30 min was 95% in animals with or without the infusion of 50-60 ml isotonic saline/kg body weight in 1½–2½ hrs. Comparable infusion of 0.04 M adenosine monophosphate reduced the incidence to 53% (p < 0.01). Arcaine was ineffective even at a toxic concentration. Injection of up to 180 mg phenylbutazone, 25 mg sodium salicylate, or 8.5 mg acetylsalicylic acid (ASA) per kg did not affect the incidence of occlusive thrombosis, but from 15 to 100 mg ASA per kg reduced the incidence to 46% (p < 0.01). Suspensions of connective tissue or collagen particles caused somewhat greater release of platelet-bound 14C-serotonin in heparinized than in citrated, platelet-rich rabbit plasma, and ASA more readily inhibited connective tissue- or collagen-induced aggregation in the latter. With varying connective tissue concentrations, this drug caused a constant reduction in the amount of 14C-serotonin released from the platelets in citrated, platelet-rich rabbit plasma, whereas considerably greater inhibition was observed in many samples of citrated, platelet-rich human plasma.